Systematic Analysis of the Effect of Good Corporate Governance on Financial Statement Fraud in Indonesia - Evianti, Dessy; Rahmiyati, Nekky; Mayndarto, Eko Cahyo; Puspa, Eka Septariana (Pt. Anagata Sembagi Education, 2025)
Financial statement fraud is a crucial issue that reflects weak internal control and corporate governance. This study aims to analyze the effect of Good Corporate Governance (GCG) on financial statement fraud through a Systematic Literature Review (SLR) approach. The search was conducted on articles published in the last five years with a focus on GCG elements such as independent board of commissioners, audit committee, institutional ownership, and managerial ownership. The study results show that most GCG elements negatively affect financial statement fraud, although there are contradictory findings that suggest that GCG effectiveness is contextual. Factors such as firm size, industry sector (Islamic or non-financial), and quality of implementation strongly influence the strength of the relationship between GCG and fraud. The study also identified that the integration of GCG with internal audit function and corporate ethical culture is a more effective combination in preventing fraud. This study makes a theoretical contribution by reinforcing the understanding that the relationship between GCG and financial statement fraud is not linear or uniform, but rather highly dependent on the institutional context and governance practices implemented in the business environment in Indonesia.